POTENSI ALERGI AKIBAT INFEKSI Anisakis typica PADA DAGING IKAN CAKALANG - Lady Cindy Soewarlan (Jurnal Teknologi dan Industri Pangan, 2016)
Anisakid larvae are zoonotic parasites that can cause allergy in human consuming infected raw fish. This research aims to identify the allergenic potential of skipjack flesh infected by Anisakis typica larvae stage 3 (L3). Identification was done through antigen detection in protein profile of the fillet. Samples from the white part of the skipjack flesh of both infected and non-infected flesh, as well as L3 A. typica were analysed using SDS PAGE. Futhermore, the molecular weights from the analysis were compared to the literature references of protein profile. The result showed that both samples have 8 similar bands of protein, but 4 bands were found only from the infected fish. The four bands of 212, 66, 59 and 44 kDa were antigens of L3 A. typica. The presence of antigen from L3 A. typical in the infected flesh may induce allergy when the fish is consumed.